Rational synthesis of Mo(1−x)WxY2 (Y = S, Se) nanowire alloys and their electrochemical catalytic activities. (15th November 2019) - Yang, Lei; Zhang, Wen; Li, Ruixin; Wang, Qunxin; Liu, Ping; Li, Jing; Feng, Chao; Yuan, Xueqin
Abstract: Transition metal dichalcogenides (TMDs) have attracted considerable attention in hydrogen evolution reaction (HER) due to their abundant earth reserves and comparable catalytic activity to Pt. The effective methods to improve the electrocatalytic activities of TMDs include increasing the density of exposed active edge sites and optimizing the electronic structure. Here, we report the synthesis of Mo(1−x) Wx Y2 (Y = S, Se) nanowire alloys with high exposed active edge sites by using an electrospinning method with subsequent sulfuration or selenization process. The morphologies and structures of the samples were characterized by the scanning electron microscopy, transmission electron microscopy and x-ray diffraction. Raman scattering and x-ray photoelectron spectroscopy characterizations revealed that the composition of the ternary Mo(1−x) Wx Y2 (Y = S, Se) nanowire alloys could be tuned by varying the W content of the precursors. Compared to pure MoS2 (WS2 ) nanowires and MoSe2 (WSe2 ) nanowires, the introduction of W (Mo) atoms can lead to enhanced catalytic activities in HER.